Five-Year Trend Analysis of Blood-Borne Disease Screening Results in Shiyan, Hubei Province, China (2019-2023): A Time Series Study - Zhang, Xuan; Tian, Fang (International Journal of Public Health and Medical Research, 2024)
This study aims to analyze the temporal trends of blood-borne disease (hepatitis B, hepatitis C, HIV, and syphilis) screening results in Shiyan City, Hubei Province, from 2019 to 2023. The research is based on five years of monthly screening data from the Shiyan Central Blood Station, utilizing time series analysis methods including trend analysis, seasonal analysis, and ARIMA modeling. Results show that the screening positivity rates for hepatitis B and hepatitis C demonstrate a slow declining trend, while the positivity rates for HIV and syphilis remain relatively stable. All diseases exhibit significant seasonal fluctuations, with higher detection rates in summer. The study also finds that the COVID-19 pandemic in early 2020 had a significant impact on screening work, leading to a temporary decrease in testing volume. This research provides important evidence for understanding the prevalence trends of blood-borne diseases in Shiyan City, offering references for local blood safety management and public health decision-making, and potentially providing methodological insights for similar studies in cities of comparable scale.